Sleeping Beauty - Geronimi, Clyde; Costa, Mary; Shirley, Bill, 1921-1989; Audley, Eleanor; Perrault, Charles, 1628-1703. (Burbank, CA : Walt Disney Home Entertainment, 2008)
Princess Aurora is doomed to die from a curse on her sixteenth birthday, but a good fairy alters the curse to have her fall into a deep sleep, to be awakened only by the kiss of her true love.
Based on the story "Belle au bois dormant" by Charles Perrault.
Originally released as a motion picture in 1959.
Features: Disney's Fastplay, never-before-seen alternate opening, all-new game: "Briar Rose's waltz," all-new music video, all-new making of Sleeping Beauty featurette, deleted songs.
Voices: Mary Costa, Bill Shirley, Eleanor Audley, Verna Felton, Barbara Luddy, Barbara Jo Allen, Taylor Holmes, Bill Thompson.
MPAA rating: G.
DVDs, Dolby digital 5.1 surround.
Keywords: Perrault, Charles, -- 1628-1703 -- Film and video adaptations; Sleeping Beauty (Tale) -- Drama; Princesses -- Drama; Fairy plays; Spinning-wheel -- Drama; Magic -- Drama; Sleep -- Drama; Video recordings for the hearing impaired; Fiction films; Based on the book; Feature films; Fairy tales; Fantasy films; Romance films; Animated films